The Societal Responses to Covid-19: Evidence from the G7 Countries - Katharina Lima de Miranda; Dennis J. Snower (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper provides a new picture of how countries have responded to the COVID-19 pandemic by examining the effects of the pandemic in terms of normative foundations for societal wellbeing. Social prosperity depends primarily on the functioning of four domains: the economy, the state, civil society and the environment. We use the Recoupling Dashboard—composed of four main indexes: Solidarity (S), Agency (A), GDP (material Gain, G) and Environmental sustainability (E) —to uncover the divergent experiences of countries in 2020. This paper focuses on the G7 countries—Canada, France, Germany, Italy, Japan, the United Kingdom, and the United States—as the first step towards a wider appraisal. In all countries under review we see a sharp drop in GDP due to the pandemic and a corresponding drop in CO2 emissions. The uniformity of response in the economic and environmental domains stands in sharp contrast to the diversity of social responses to the challenge of cooperation that the coronavirus posed. The only clear pattern that emerges from cross-country comparisons is that Inward Solidarity, important for social cohesion in close social networks, and Outward Solidarity, important for the will to cooperate with other nations and cultures, have drifted apart in all G7 countries except Japan. Otherwise the movements in solidarity are highly idiosyncratic. In addition, the responses of Agency to the pandemic are diverse and are not noticeably correlated with the changes in Solidarity. The discrepancies in the social responses to the pandemic may be expected to have potentially important implications for how these countries fare during the pandemic and how well they come out of this crisis.
Keywords: 330; Covid-19; wellbeing; social sustainability; social solidarity; empowerment; beyond GDP